Nanostructured tungsten trioxide on interdigitated microelectro- mechanical platform for ethylene gas sensor applications / Amirul Abd Rashid - Abd Rashid, Amirul (Institute of Graduate Studies, UiTM, 2017)
In this study, tungsten trioxide (WO3) nanostructure material is integrated onto interdigitated (IDE) Micro-electro-mechanical (MEMS) platform to form a gas sensor targeting to detect ethylene gas. Traditionally, ethylene gas detection requires the sample of the gas to be collected and measured offline due to the complexity of the measurement system. Even though a newer detection technology which enables for in-situ detection has been developed, the size of the sensor is relatively bulky and very expensive hence it is not suitable for mass outdoor applications examples in the agriculture industry. Therefore, this research explores a different approach to detecting ethylene gas utilizing WO3 nanostructure as the sensing element of the sensor. This n-type metal oxide family were recognized for its excellent in sensitivity, ruggedness, versatility and relatively low cost to fabricate compared to other gas sensing material technology. The early work in this research is focused on producing one-dimensional WO3 nanostructure through hydrothermal method. Design of experiment (DOE) technique is used to identify the effect and relationship of the variables in producing WO3 nanostructure morphology. Field Emission Scanning Electron Microscopy (FESEM) reveals one dimensional, two dimensional and three-dimensional nanostructures have been produced by this facile process. Since the response of the gas sensor is highly dependent on the surface area, the analysis of DOE was focused on defining parameters that will produce one-dimensional nanostructure because it will give the biggest surface to volume ratio compared to the other structures. This type of morphology is also suitable to create the electrical interconnection in between the IDE electrodes to functionalist the sensor…